Influence of Y–Bi–Co oxide doping on electrical performance of ZnO varistors based on simulation analysis - Zhengzheng Fu; Zongxi Zhang; Songhai Fan; Tao Cui; Donghui Luo; Yue Yin; Pengfei Meng; Jingke Guo (International Journal of Ceramic Engineering & Science)
Abstract ZnO varistors doped with Y2O3, Bi2O3, and Co2O3 were analyzed for electrical performance, microstructure, phase composition, and elemental distribution using electrical performance testing, scanning electron microscopy, X‐ray diffraction, and energy dispersive spectroscopy tests. The best results were obtained with 0.5 mol% Y2O3, 2 mol% Bi2O3, and 3 mol% Co2O3, yielding a 356 V/mm voltage gradient, 0.9 μA leakage current, and a nonlinear coefficient of 66.2. The Voronoi network model explained how Bi2O3 and Co2O3 enhance Y‐doped varistor performance. Grain size was identified as the primary factor affecting the voltage gradient, while the thick grain boundary phase impedance, the direct contact area ratio, surface state density, and donor density were key factors influencing the nonlinear coefficient and leakage current. The results indicate that doping with Bi2O3 and Co2O3 significantly enhances the electrical properties of Y‐doped varistors, and simulation methods effectively reveal the effect mechanisms of dopants on the varistors.